Glucose transporter type 1 deficiency syndrome and the ketogenic diet. Issue 2 (13th November 2019) - Schwantje, Marit; Verhagen, Lilly M.; van Hasselt, Peter M.; Fuchs, Sabine A.
Abstract: Glucose transporter type 1 deficiency syndrome (GLUT1DS) is characterised by deficient glucose transport over the blood‐brain barrier and reduced glucose availability in the brain. This causes epilepsy, movement disorders, and cognitive impairment. Treatment with ketogenic diet provides ketones as alternative energy source. However, not all GLUT1DS patients are on dietary treatment (worldwide registry: 77/181 [43%] of patients). The current 25‐year experience allows evaluation of effects and tolerability of dietary treatment for GLUT1DS. To this end, literature was searched up to January 2019 for individual case reports and series reporting (side) effects of dietary treatment for GLUT1DS. Upon aggregation of data for analysis, we identified 270 GLUT1DS patients with dietary treatment with a mean follow‐up of 53 months. Epilepsy improved for 83% of 230 patients and remained unchanged for 17%, movement disorders improved for 82% of 127 patients and remained unchanged for 17%, and cognition improved for 59% of 58 patients and remained stable for 40%. Effects on epilepsy were seen within days/weeks and were most pronounced in patients with early treatment initiation. Effects on movement disorders were noticed within months and were strongest in patients with higher cerebrospinal fluid‐to‐blood glucose ratio. Although side effects were minimal, 18% of 270 patients reported poor compliance. In individual patients, symptoms deteriorated upon low ketosis, poor compliance, or treatment discontinuation. Based on the good tolerability and strong favourable effect of dietary treatment on GLUT1DS symptoms, we advocate dietary treatment in all GLUT1DS patients and prompt diagnosis or screening to allow early treatment.